Understanding the evolution of the fiscal situation of the Brazilian states; 2006–2015 - José Luiz Rossi Júnior; Fernando Aguiar (EconomiA, 2018)
The text analyzes how the Brazilian states' fiscal position evolved between 2006 and 2015, with the data revealing a clear deterioration in state-level public finances during that period. The rating methodology developed by the Ministry of Finance is used to show that, when comparing 2006–2008 to 2013–2015, 21 of the 26 states and the Federal District saw their fiscal position deteriorate. The results suggest that after the global financial crisis the states failed to pursue a fiscal rule that would curb the growth of spending in a context of falling revenue and rising debt. The study shows that, despite shrinking revenue, the states maintained the pace of expenditure growth, particularly payroll and pension expenses. Moreover, the text shows that following the crisis, state-level revenue would have declined by even more were it not for a substantial increase in credit inflows. While additional borrowing enabled the states to maintain public investment in the short term, this policy showed to be unsustainable. The paper shows that higher debt and the lack of the adjustment in public spending have a negative impact on state-level investment in the long term.
Keywords: 330; Fiscal rules; Brazil; Federalism